Contact Tracing during Coronavirus Disease Outbreak, South Korea, 2020 - Park, Young Joon; Choe, Young June; Park, Ok; Park, Shin Young; Kim, Young-Man; Kim, Jieun; Kweon, Sanghui; Woo, Yeonhee; Gwack, Jin; Kim, Seong Sun; Lee, Jin; Hyun, Junghee; et al. (Emerging infectious diseases, 2020)
We analyzed reports for 59,073 contacts of 5,706 coronavirus disease (COVID-19) index patients reported in South Korea during January 20-March 27, 2020. Of 10,592 household contacts, 11.8% had COVID-19. Of 48,481 nonhousehold contacts, 1.9% had COVID-19. Use of personal protective measures and social distancing reduces the likelihood of transmission.